Implementation of Sustainable Finance and Corporate Financial Performance: A Systematic Literature Review - Pra Gemini; Hasliah Hasliah; Fausiah Fausiah; Aminah Aminah; Andi Herman Tellu; Elisabeth Ambalele (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The growing integration of Environmental, Social, and Governance (ESG) considerations into corporate strategy has made sustainable finance a prominent research topic, yet its relationship with corporate financial performance remains inconclusive across industries and countries. This study aims to systematically review existing empirical evidence on the implementation of sustainable finance and its effects on corporate financial performance. A systematic literature review method was employed, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses framework. A total of 34 peer-reviewed articles published between 2015 and 2026 were selected from multiple academic databases through a structured screening process. The findings reveal that sustainable finance practices, including environmental, social, and governance integration, sustainability reporting, green financing, and climate-risk management, are generally associated with improved profitability, stronger market valuation, and better access to capital. However, mixed and negative outcomes were also identified, particularly in contexts where sustainability risks are poorly managed or where regulatory environments are underdeveloped. The review further highlights emerging research trends, including the growing role of mediation and moderation mechanisms in explaining the sustainable finance–performance relationship. These findings carry practical implications for managers, policymakers, and future researchers in the field of sustainable corporate finance.